THE CONCEPT OF NEW LITERACY IN OFFICIAL CURRICULAR DOCUMENTS IN THE STATE OF PARANÁ, BRAZIL - Jane Cristina Beltramini Berto; Jonathas de Paula Chaguri (Universidade Federal de Sergipe, 2018)
This work aims to analyze the concept of new literacy in Curricular Guidelines of Portuguese Language in the State of Paraná, Brazil (Diretrizes Curriculares de Língua Portuguesa do Estado do Paraná, DCE-LP) (PARANÁ, 2008), concerning its process of elaboration after the previous curriculum documents, DCE-LP of 2006, and the Paraná Basic Curriculum of 1990, in order to verify their consonance with theories postulated by Street (1989; 2003), Soares (2000; 2004), and Tfouni (1994), by discussing implications to students' new literacy in public schools in Paraná, Brazil. The results point to the interweaving of literacy and new literacy studies, with emphasis on the last, aiming the teaching of writing linked to social practices. However, in the current curriculum proposal prevails the ideological model of new literacy in contrast to excerpts of the autonomous model, being far from the social practice present at curriculum proposal.